Perlindungan Hukum Terhadap Korban Pornografi Berbasis Siber - Mulyono, Dian Adiningsih; Hehanussa, Deassy Jacomina Anthoneta; Patty, Jetty Martje (PATTIMURA Law Study Review, 2025)
Cyber-based pornography crime is a form of pornography crime that uses internet information and electronic technology as a means of spreading it. This raises various problems that need to be addressed, especially regarding the protection of victims, so the author conducted research intending to find out what form of legal protection exists for victims of cyber-based pornography and the obstacles in providing legal protection for victims of cyber-based pornography. The research method used is normative juridical research using a statutory regulation approach, case approach, and conceptual approach and using qualitative analysis. The results obtained from this research are the forms of legal protection provided to victims of cyber-based pornography, namely law enforcement against perpetrators, compensation, deletion of detrimental electronic information, socialization, and cyber supervision. Obstacles in providing legal protection to victims of cyber-based pornography are limitations in regulating victims' rights in law, removing content through a long process, difficulty in identifying perpetrators, limited infrastructure, and the number of police who have expertise in the field of technology, different interpretations. different between the Pornography Law and the ITE Law.